Lethal action of bacteriophage lambda S gene. - Garrett, J M (1982)
The functions of the bacteriophage lambda lysis genes S, R, and Rz were investigated. Different combinations of wild-type and inactive alleles of all three lysis genes were cloned into the plasmid pBH20 and were expressed under the control of a lac operator-promoter. The involvement of the Rz gene in lysis was proposed in our previous work and was confirmed by the Mg2+-dependent lysis defect of clones in which part of the Rz gene is deleted. Membrane vesicles prepared from induced S+ cells were shown to have a severely reduced capacity for active transport of glucose; this defect was detectable at least 20 min before lysis. Cell viability was also shown to decrease very soon after induction, long before physiological death and lysis; this decrease in viability is absolutely dependent on S expression and independent of R and Rz. The nonviable fraction of cells at any time after induction was demonstrated to be equal to the fraction committed to eventual lysis. Induction of an Sts clone showed that the S gene product is stable and capable of inducing lysis long after the cessation of synthesis of S gene product. A model for S action is proposed.